THE RELATIONSHIP BETWEEN USE OF LEARNING FACILITIES AT HOME, INDEPENDENT LEARNING, AND DISCIPLINE LEARNING WITH MATHEMATICS LEARNING OUTCOME - Endah Kusuma Dewi; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The poor student learning outcomes associated with many factors. The use of learning facilities, independent learning, and discipline of learning are some of the factors that were related to the learning outcomes. This study aims to determine the presence or absence of a positive and significant relationship between the use of learning facilities, independent learning, and discipline of learning with mathematics learning outcomes in class VIII of even semester at Junior High School (SMP) Muhammadiyah 1 Sewon Bantul academic year 2016/2017. This research population is in a class of even semester at SMP Muhammadiyah 1 Sewon Bantul academic year 2016/2017, consisting of two classes with 53 students. The samples were taken with a random sampling technique to the classroom and derived class VIII B as a sample class with 27 students. The data collection technique used the questionnaire technique and test. Test instrument used validity test and reliability test. Test requirement analysis used a normality test, linearity test, and independence test. Analysis of data to test hypotheses used linear regression and correlation analysis. The result showed that there is a positive and significant relationship between used of learning facilities, independent learning, and discipline of learning with mathematics learning outcomes, obtained Fcount= 10,50895148 > Ftable = 3,03, multiple correlation coefficient of (R) = 0,76038772683, regression equation Â = -128,0849716 + 0,2376796668 X1 + 0,6374109258 X2 +Â  0,9547188982 X3, the relative contribution X1 = 17,37668376%, X2 = 33,77592505%, dan X3 = 48,8473912%, and the effective contribution of X1 = 10,16775925%, X2 = 19,7635797%, dan X3 = 28,58246836%.